PENGARUH MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) DAN DIRECT TEACHING TERHADAP SELF ESTEEM DAN GAYA HIDUP AKTIF SISWA SMA NEGERI 2 GARUT - Kurniawan, Asep Ridwan (2014)
The purpose of this study was to determine and test how much influence model of team learning and direct teaching tournament games against the self-esteem of students and an active lifestyle. The population in this study were students of SMAN 2 Leles and sampling techniques using random cluster sampling technique, the sample in this study is a class X (ten). The method used is the method of experimental research design was pretest-posttest control group design. Instrument in this study is to use a variable active lifestyle active lifestyle questionnaire consisting of 10 items of the question. Variables for self esteem is developed by Coopersmith with "Self Esteem Inventory" (SEI). The results of this study are the differences in the variables of self-esteem between models of learning teams tournament games direct teaching and learning with t value is 0,525 and the probability value 0,007 < 0,05, the hypothesis is accepted or there are significant differences in the variables of self-esteem between models of learning and team games tournament teaching direct learning. Then the difference in the active lifestyle variables between tournament games team teaching model and teaching direct learning with t value is 2,222 and the probability value 0,029 < 0,05, the hypothesis is accepted or there are significant differences in the variables of self-esteem between models of learning and teaching team tournament games direct teaching. Furthermore, to test the difference between self-esteem and active lifestyle on teaching models and learning team games tournament known direct teaching calculated F (68,812) and the probability value 0,000 < 0,05 then the hypothesis is accepted or there are differences in self-esteem and active lifestyle among students who taught learning model Games Tournament Team (TGT) and students who are taught with the Direct teaching learning model. The conclusion of this study that the learning model team games tournament Direct Teaching and learning models affect the increase in self-esteem and lifestyle student SMAN 2 Garut. Recommendations are expected by the researchers that researchers suggest to school, especially high school physical education teacher School 2 Garut should further improve the understanding of the application of learning models Team Games Tournament for the benefit of the model is able to improve the understanding of learning are presented. Tujuan penelitian ini adalah untuk mengetahui dan menguji seberapa besar pengaruh model pembelajaran team games tournament dan direct teaching terhadap self esteem dan gaya hidup aktif siswa. Populasi pada penelitian ini adalah siswa SMA Negeri 2 Leles dan teknik pengambilan sampel menggunakan teknik cluster random sampling, sampel pada penelitian ini yaitu kelas X (sepuluh). Metode yang digunakan adalah metode eksperimen dengan desain penelitian adalah Pretest-posttest Control Group Desain. Instrumen pada penelitian ini adalah untuk variabel gaya hidup aktif menggunakan angket gaya hidup aktif yang terdiri atas 10 item pertanyaan. Variabel untuk self esteem yang dikembangkan oleh Coopersmith dengan "Self Esteem Inventory" (SEI). Hasil Penelitian ini adalah perbedaan pada variabel self esteem antara model pembelajaran team games tournament dan pembelajaran direct teaching dengan nilai t hitung 0,525 dan nilai probabilitas adalah 0,007 < 0,05 maka Ho ditolak atau terdapat perbedaan yang signifikan pada variabel self esteem antara model pembelajaran team games tournament dan pembelajaran direct teaching. Kemudian perbedaan pada variabel gaya hidup aktif antara model pembelajaran team games tournament dan pembelajaran direct teaching dengan nilai t hitung 2,222 dan nilai probabilitas adalah 0,029 < 0,05 maka Ho ditolak atau terdapat perbedaan yang signifikan pada variabel self esteem antara model pembelajaran team games tournament dan pembelajaran direct teaching. Selanjutnya untuk uji beda antara self esteem dan gaya hidup aktif pada model pembelajaran team games tournament dan pembelajaran direct teaching diketahui F hitung (68,812) dan nilai probabilitas 0,000 < 0,05 maka Ho ditolak atau terdapat perbedaan self esteem dan gaya hidup aktif antara siswa yang diajar dengan model pembelajaran Team Games Tournament (TGT) dan siswa yang diajar dengan model pembelajaran Direct Teaching. Kesimpulan dari penelitian ini bahwa model pembelajaran team games tournament dan model pembelajaran Direct Teaching berpengaruh terhadap peningkatan self esteem dan gaya hidup siswa SMA Negeri 2 Garut. Rekomendasi yang diharapkan oleh peneliti yaitu Peneliti menyarankan kepada sekolah terutama guru pendidikan jasmani sekolah SMA Negeri 2 Garut harus lebih meningkatkan kembali pemahaman mengenai penerapan model pembelajaran Team Games Tournament karena manfaat dari model tersebut mampu meningkatkan pemahaman mengenai pembelajaran yang disampaikan. Kata Kunci: team games tournament, direct teaching, self esteem, gaya hidup aktif